The Knowledge and Awareness about the Effect of Polypharmacy on Renal Function among Adults in Saudi Arabia (Asian Journal of Pharmaceutics (AJP), 2026)
Background: Polypharmacy, the concurrent use of multiple medications, is a common issue, particularly in older adults. It can lead to adverse effects like renal function decline. Research in Japan found a link between more prescribed drugs and a faster decline in kidney function. Studies in Egypt and Saudi Arabia highlighted a lack of awareness about polypharmacy among elderly populations. However, no research in Saudi Arabia has assessed people’s knowledge of polypharmacy’s impact on renal function. Objectives: The aim of this study is to assess the knowledge of adults in Saudi Arabia regarding the effect of polypharmacy on renal function. Methodology: This observational cross-sectional study was conducted from November 2023 to September 2025 in Saudi Arabia. Our study population consisted of Saudi men and women aged 18 years and above. Our sample size is a minimum of 384 participants. Microsoft Office Excel (2019) was used to enter, save, and code the data that was gathered through the questionnaire. The Statistical Package of Social Science Software, version 26 for Windows, was used for all statistical analyses.